IMPLEMENTATION OF THE THINK PAIR SHARE (TPS) LEARNING MODEL IN IMPROVING STUDENT LEARNING OUTCOMES IN THE SUBJECT OF ISLAMIC CULTURAL HISTORY FOR CLASS V AT MIN 2 WEST PASAMAN - Novrita, Zahwa; Oktarina, Risqa; Hanifah, Nisaul; Mawadah Rohmah, Mutia (Mandeh : Jurnal Pendidikan Islam, 2026)
This study aims to determine the application of the Think Pair Share (TPS) learning model in improving student learning outcomes in the History of Islamic Culture (SKI) subject for fifth graders at MIN 2 West Pasaman. The background of this study is the low student learning outcomes in SKI, caused by a lack of student participation, courage, and motivation in the learning process. The TPS model was chosen because it includes cooperative learning steps that emphasize individual thinking (think), pair discussions (pair), and large group sharing (share). This research is a quantitative study with a pre-experimental approach (one group pretest-posttest design). The subjects were all 28 fifth grade students at MIN 2 West Pasaman. Data collection techniques included observation, questionnaires, documentation, pretests, and posttests. Data were analyzed using the learning mastery formula (KB) and the percentage of teacher and student responses. The results indicate that the TPS model was implemented effectively. Based on the questionnaire, 62.5% of students stated that it was easier to understand the Social Sciences (SKI) lesson and 57.5% felt more confident expressing their opinions after participating in the TPS learning model. Teachers also assessed TPS as quite effective (70%) in improving student understanding, fostering courage, and creating a conducive learning environment. Based on the learning outcomes, before the TPS implementation (pretest), only 7 of 28 students (25%) achieved the Minimum Completion Criteria (KKM = 75). After the TPS implementation (posttest), all 28 students (100%) achieved the KKM, resulting in a 75% increase in completion.